Features of vestibular resistance in aggressive and nonaggressive students of humanitarian university - Romanenko Valerij Aleksandrovich; Prikhodko Vladimir Mikhajlovich; Sokolova Viktoriia Yur'evna; Ivanova Svetlana Dmitrievna (Kharkov National Pedagogical University, 2011)
Present the results of determining the stability of the organism levels of students with polar aggressiveness on the vestibular tests with angular accelerations. It is shown that the stability of aggressive students is reduced by 29.3%. This is due to insufficient cost-effective functioning of the circulatory system in basal conditions. It is established that a certain strain the cardiovascular system is an integral part of their genetic aggressiveness and reflects the willingness to act. It is shown that aggressiveness (as a character trait) should be considered as a determinant of reduced stability of the individual to angular accelerations.